DEVELOPMENT OF ELECTRONIC MODULES WITH ANDROID EBOOX APPLICATIONS ON BASIC COMPETENCIES MAINTENANCE OF SAFETY SYSTEMS - Mujahidin, Zaki Ahmad; Sukrawan, Yusep; Permana, Tatang (Universitas Pendidikan Indonesia, 2023)
This study aims to create an electronic module for maintaining a security system with readings using the ebook application and to determine the feasibility and response of students as users of this developed module. This study uses the type of research and development with the ADDIE model for the module development process and analyzes research data using quantitative and descriptive methods. The population in this study was shown to class XI students majoring in Automotive Light Vehicle Engineering at Vocational High School 6, Bandung City, and the sample chosen was class XI-2, which used electronic modules for maintenance of safety systems. The instruments used include media expert assessment questionnaires to assess the feasibility of learning module products and student response questionnaires to find out students' responses regarding the use of these modules. The results of this study show that the assessment of the module by material experts gets a percentage value of 90% and can be categorized as